The Parliament of North Macedonia in the Advent of Accession Negotiations with the European Union: Bystander or Actor? - Kocevski, Goce (Central European Academy Law Review, 2025)
This paper analyses the role of the national parliament (Assembly) of North Macedonia in the process of the country’s accession to the European Union. In 2022, North Macedonia started the opening phase of the accession negotiations. However, its closure is conditioned. The country must amend its Constitution to include the Bulgarian minority as an ethnic group. This requirement has put the Assembly under the spotlight. The integration of the country into the EU depends on enacting these amendments. Yet, the role of the Assembly does not end here. The paper describes the prerogatives of the Assembly in the context of EU accession, with a focus on the alignment of legislation and political oversight of the executive. It also analyses the specialised parliamentary bodies on EU affairs. The objective of the research is to assess to what extent the Assembly is using its constitutional prerogatives to give legitimacy to the process of EU accession that is overwhelmingly run by the executive. The author analysed data on the performance of the Assembly over the past ten years. The findings showed an overuse of the fast-track procedure for the harmonisation of legislation. The political oversight remains weak, although the special bodies within the parliament are meeting more frequently compared with the previous period. The Parliament is not part of the negotiation structure adopted by the Government, however, the chief negotiator is obliged to report to the Parliament about the progress. The role of the Parliament can be strengthened by a detailed regulation of the procedure for adopting laws for the transposition of EU law and by more frequent hearings in the specialised parliamentary bodies.